The Domestication and Arabization of the Bard: Towards the Reception of Shakespeare in the Arab World - Hassoon, Mohammed Naser (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
Since Najib al-Haddad and Tanyusʻ Abdu’s first Arabic versions of Romeo and Juliet and Hamlet at the end of the 19th century, the reception of Shakespeare in the Arab world has gone through a process of adaptation, Arabization, and translation proper. We consider the process of Arabization / domestication of Shakespeare’s plays since Najib al-Haddad’s adaptation of Romeo and Juliet and Tanyusʻ Abdu’s adaptation of Hamlet, to the achievements of Khalīl Mutran and Muhammad Hamdi. We underline, as particular examples of Shakespeare’s appropriation, the literary response of Ali Ahmed Bakathir, Muhammad al-Maghut and Mamduh Udwan, with a particular stress on Khazal al-Majidi and his adaptations of Shakespeare’s plays. All these writers reposition Shakespeare’s plays in an entirely different cultural space.